2018
DOI: 10.1002/gcc.22702
|View full text |Cite
|
Sign up to set email alerts
|

Cancer diagnosis and immunotherapy in the age of CRISPR

Abstract: The explosion in genome editing technologies that has occurred in the past decade has revolutionized cancer research and promises to improve cancer diagnosis and therapy. Ongoing efforts include engineering of chimeric antigen receptor‐T cells using clustered regularly interspaced short palindromic repeats (CRISPR) to generate a safer, more effective therapy with improved performance in immunologically “cold” tumors, as well as clever adaptations of CRISPR enzymes to allow fast, simple, and sensitive detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…To demonstrate the potential application value of RCH, it was applied to detect circulating let-7a in serum samples from patients with non-small cell lung cancer (NSCLC) and healthy volunteers. As it was reported that since the expression of circulating let-7a was significantly down-regulated in patients with NSCLC, it could become a useful biomarker for NSCLC[ 41 ]. It was also discovered that the detection results were highly consistent with RT-PCR results and the literature reports, suggesting that this method could be used for the screening and diagnosis of tumors in the near future.…”
Section: Clinical Application Of Crispr/cas Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the potential application value of RCH, it was applied to detect circulating let-7a in serum samples from patients with non-small cell lung cancer (NSCLC) and healthy volunteers. As it was reported that since the expression of circulating let-7a was significantly down-regulated in patients with NSCLC, it could become a useful biomarker for NSCLC[ 41 ]. It was also discovered that the detection results were highly consistent with RT-PCR results and the literature reports, suggesting that this method could be used for the screening and diagnosis of tumors in the near future.…”
Section: Clinical Application Of Crispr/cas Technologymentioning
confidence: 99%
“…While the SHERLOCK and SHERLOCKv2 molecular detection platforms can detect the BRAF V600E mutation in simulated circulating DNA samples and the EGFR L858R mutation in liquid biopsy samples from adenocarcinoma patients[ 26 , 29 , 43 ], the DETECTR method can also be used to rapidly detect tumor mutations in the reproductive system[ 30 ]. For example, human papillomavirus, closely related to the occurrence of cervical cancer, is detected in human anal wipe DNA extracts[ 41 ]. The development of this technology is expected to bring a significant breakthrough in the early screening of cervical cancer (Table 3 ).…”
Section: Clinical Application Of Crispr/cas Technologymentioning
confidence: 99%
“…Secondly, although various approaches have been reported to improve gRNA design ( Bin Moon et al, 2018 ; Matson et al, 2019 ; Han et al, 2020 ) and increase the specificity of Cas enzyme ( Kleinstiver et al, 2016 ; Slaymaker et al, 2016 ), the risk of off-target effects, resulting from non-specific cutting and further leading to unwanted mutations, still remains a major obstacle to translation of CRISPR/Cas9 system to clinical therapeutic use ( Cook and Ventura, 2019 ). Whereas, in clinical trials, no significant or only a small number of off-target sites, chromosomal rearrangements or long-range deletions were actually detected.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…So, in designing gRNAs, genetic variabilities among individuals should be taken into consideration. 50 …”
Section: Crispr/cas Systemmentioning
confidence: 99%